PENGARUH GAYA KEPEMIMPINAN, MOTIVASI, BUDAYA ORGANISASI DAN LINGKUNGAN KERJA TERHADAP KINERJA PEGAWAI PADA KECAMATAN KREJENGAN KABUPATEN PROBOLINGGO - Yoga Arif Wicaksono; Martaleni; Rini Astuti (Faculty of Islamic Economics and Business, 2022)
Employee performance is the result of work in quality and quantity achieved by an employee in carrying out his duties in accordance with the responsibilities given to him. Factors that affect performance are leadership style, motivation, organizational culture and work environment. Based on this, this research study aims to determine and analyze the influence of leadership style, motivation, organizational culture and work environment on employee performance in Krejengan District, Probolinggo Regency. The type of research used in this study is descriptive research using quantitative methods and approaches that describe the influence of leadership style, motivation, organizational culture and work environment on employee performance in Krejengan District, Probolinggo Regency. The total population in this study were all employees of the Krejengan sub-district, Probolinggo Regency, as many as 43 people. Sampling in this study used saturated sampling, the entire population was used as a sample of 43 people. The results showed that 1) Leadership Style had a significant effect on employee performance, 2) Motivation had no significant effect on employee performance, 3) Organizational Culture had no significant effect on employee performance, 4) Work environment had a significant effect on employee performance, 5 ) Leadership style is the most dominant factor that has a significant effect on employee performance. Organizational climate provides environmental forces that can affect the organization.